The Correlation of Business Creativity and Social Media with MSMEs Entrepreneurial Performance - Dekeng Setyo Budiarto; Mei Islamiyati; Muhammad Agung Prabowo (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2021)
Micro Small and Medium Enterprises (MSMEs) in Indonesia plays a significant role in economic growth, especially by creating employment opportunities and, at the same time, reducing the unemployment rate. Small firms are high potential enterprises that need improvement in order to contribute to either micro- or macro-economic development in this country. Entrepreneurs need to strengthen their competitive advantage to ensure their long-term survival. Small firms face significant challenges that require them to devise an effective strategy to improve performance. The present study aims to investigate whether business creativity and social media among MSMEs correlate with entrepreneurial performance. The sample consisted of 120 MSMEs in the Special Region of Yogyakarta selected using the purposive sampling method. Respondents are owners or managers authorized with the responsibility for the survival of their enterprises. The results show that MSMEs entrepreneurs are using Instagram and that creativity-based MSMEs have better business entrepreneurial performance. The results imply that MSMEs entrepreneurs need to promote their products on social media and to improve their creativity to boost their business performance